L'idéologie marchande au service de la biodiversité ? - Tordjman, Hélène; Boisvert, Valérie (Mouvements, 2012)
Economics
Keywords: biodiversity; markets

Retour sur le désencastrement - Brisset, Nicolas (Revue européenne des sciences sociales. European Journal of Social Sciences, 2012)
Our ambition is to point out that a fresh look at what is usualy considered to be Karl Polanyi’s magnum opus, The Great Transformation, opens some new prospects on its analytical. This interpretation qualifies some of the Hungarian author’s main critics, directed against his concept of desembeddedness. With this aim in mind, we re-interpret this debate in epistemological terms, i.e. the link between concepts and reality ; then we try to connect Karl Polanyi with the notion of performativity, which is today flourishing, above all within the field of economic sociology.
Economics
Keywords: Great Transformation; The (Book); Karl Polanyi; disembeddedness; great transformation; performativity; realism

Crise ? Vous avez dit : « Crise » ? - Naszályi, Philippe (Revue des Sciences de Gestion, 2012)
Crisis and institutional environment, crisis and organisational anticipations and crisis and consumer behaviour, just a few of the uses of the word « crisis » ; a word which, for over four years now, for the less perspicacious, and for over thirty years, for those who have been watching the bigger picture, has been the most appropriate word for this stage of development of the contemporary economic system. But exactly « what crisis are we talking about? ». That which is the result of a system, of an ideology which inhabits this system and of which the slightest of abilities was to try and present itself as unable to be exceeded, « by the end of the story ».' Yet, just as Max Weber stated, it seems that today's knowledge is still destined to be exceeded, particularly in the humanities, since society is constantly undergoing transformation. There is, therefore, no economic model which should not be discussed in order to be improved, or replaced. By delving into the ideal of Sismondi, today wrongfully forgotten, or in studying Karl Polanyi, we can gain much support for contemporary reflection which cannot continuously oppose Keynes, often summarised to the deficit of public policies and the « Chicago Boys » of which the action with Augusto Pinochet is truly symbolic of this « neo-liberalism» of American conservatives which is spreading across the globe, despite the crises which it has created. Crisis? Did you say: « Crisis' ? A question, and observation, but also in the manner of «great thinkers », solutions and alternatives which managers, in the widest sense of the term, « those who look after others and their businesses », provide through thirteen articles, collated into three thematic sections in this Spring edition which opens up new areas for reflection and action as « it is indeed time to put production before speculation, future investment before current satisfaction, sustainable employment before immediate profiteering ». (English)
Economics
Keywords: WEBER; Max; 1864-1920; consumer behavior; economic models; economic systems; humanities; institutional environment